IMPACT OF Plasmodium falciparum PARASITAEMIA ON SOME HEMATOLOGICAL PROFILES AMONG CHILDREN 6-59 MONTHS: A CASE STUDY OF SELECTED HOSPITALS IN MAIDUGURI, BORNO STATE, NIGERIA - Inuwa, Yahaya; Chessed, Godly; Qadeer, Muhammed A.; Suleiman, Abubakar; Bukar, Ahmed S.; Mustapha, Adam; Kokori, Mustapha (FUDMA JOURNAL OF SCIENCES, 2023)
Plasmodium falciparum is responsible for millions of deaths globally, with children under five years old the most vulnerable. It is associated with some haematological changes. As a result, this study was carried out to evaluate the effects of P. falciparum parasitaemia on certain haematological parameters in Malaria-affected Children in Maiduguri. To ascertain the prevalence and haematological alterations brought on by infection, blood samples were taken from 421 kids during the months of December 2021 and June 2022 (7 months). Overall results show 182 (43.23%) patients were positive to malaria while 239 (56.77%) were negative. Similarly, the PCV, RBC and thrombocytes count respectively (23.95%, 2.94 x 10-9/µL and 346.23 x 10-9/µL and 147.15 x 10-9/µL) of the malaria positives subjects were significantly (P=0.05) lower compared to the malaria negative (34.69%, 4.0 x 10-9/µL and 346.23 x 10-9/µL) subjects. Furthermore, the mean WBC, lymphocytes and neutrophils respectively of the malaria positive subjects were significantly higher compared (18.67 x10-9/µL, 59.88% and 66, 05%) to the infected ones (12.92 x 10-9/µl, 37.69% and 47.05%). The result also shows the mean of sex comparison of haematological  parameters of children infected with malaria, with the PCV and thrombocytes of male positive subject been significantly lower than that of the female negative children (24.40% and 145.98 x 10-9/µ) versus (34.82% and 337.00 x 10-9/µl) appropriately (p=0.05), whereas the mean WBC, lymphocytes and neutrophils were significantly higher compared to female...